Prática de leitura de canções : o empoderamento feminino - Jesus, Joseneide Santos de (2019)
The current TCF aims to present a pedagogical proposal of critical reading through songs of female authorship that detach the hole of independence and woman’s empowerment, portrayed in the letters of the songs “Desconstructing Amelia”, by Pitty, “Respect the girls”, by Kell Smith, “Respect”, by Ana Cãnas, “Pagu”, by Zelia Duncan and Rita Lee and “Balacobaco”, de Rita Lee. These authors discuss and question the woman space in the society in her fight for rights. This approach does part of an intervention work developed in the classes of Portuguese Language of a class of ninth year of a municipality school in Jeremoabo/BA. It is organized in a theoretical part and other methodological. In the first part, we focus the debate about the “Formation of the reader and the literary text” and the “Relations of gender and female empowerment”, while in the second one, we described the practical realization of our work: “literary workshops – discussing the female’s empowerment and analysis of the results”. In relation to the theoretical framework, we present fundamental concepts about the work with the literary text and the formation of the reader, based on the studies about cultural reading, by Carlos Gomes (2012) and the subjective reading, by Annie Rouxel (2013). We also bring Simone Alcantara’s contributions (2012), about the characterization and the importance of the gender song and Helder Pinheiro Alves (2017; 2018), in relation to poetry teaching and the insertion of production of female authorship in classroom. Already to treat of the thematic of the female empowerment, we initially bring the ideas of male domination and symbolic violence, according Pierre Bourdieu (2018); abou the construction of gender identity and its social and cultural implications, we approach Judith Butler’s theories (2014;2018), Lia Zanotta Machado (2017) and Henriqueta Moore (2000). Proceeding this perspective, we focus the importance of woman’s speaking place, based on Djamila Ribeiro (2017) and, expanding the discussion about empowerment and woman’s rights, we bring to the debate the contributions of Chimamanda Adichie (2017) and Bruna de Lara (2016). The collected datas during the research, provided the creation of a pedagogical notebook that has as main goal provide to the teacher public a practice of critical reading of songs of female authorship establishing relations with poetic and legal texts that treat of the thematic of the rights and women’s empowerment. The referred notebook is compounded for theoretical and methodological concepts that grounded the research, description of the workshops and reading script of the songs and poetries.